A framework of halal industry support system in non-Muslim country: a focus on South Korea - Park, Ming Yu; Jamaludin, Mohammad Aizat (HH Publisher, 2018)
Following the significant growth of the global halal market, not only Muslim society, but non-Muslim majority society has embraced and put effort to establish strategies to be involved in the paradigm of halal industry. However, it has been shown that accepting and embracing halal industry as a non-Muslim country has various dimensional difficulties such as social collision, lack of efficiency, and limited comprehension in the halal support system. South Korea thus far has tried to fit its halal industry into a dominantly constructed paradigm, and actively took actions to penetrate the Islamic market starting from food and beverage products with active government supports. This present work focuses on Korean halal industry with reference to the more established halal industry ecosystem in Malaysia. To study the halal ecosystem, the concept of halalan toyyiban as Shariah compliance (fundamental Islamic value system), business ecosystem theory (Moore, 1996), and Systems Theory of Political Science (Easton, 1965) have been applied as major philosophies. It was shown that a support system hierarchy encompassing the policy, system and approach level may help Korea achieve its optimal potential in halal industry. At approach level, Halal Industry Support System Sequence Map (HISSSM) is seen to be able to serve as a tool for effective intercommunication of multidimensional industry stakeholders leading to creation of synergy and improved halal industry ecosystem in Korea.